Advanced Airway Type and Its Association with Chest Compression Interruptions During Out-of-Hospital Cardiac Arrest Resuscitation Attempts. (3rd September 2017) - Jarman, Angela F.; Hopkins, Christy L.; Hansen, J. Nicholas; Brown, Jonathan R.; Burk, Christopher; Youngquist, Scott T.
Abstract: Objective : To assess interruptions in chest compressions associated with advanced airway placement during cardiopulmonary resuscitation (CPR) of out-of-hospital cardiac arrest (OHCA) victims.Methods : The method used was observational analysis of prospectively collected clinical and defibrillator data from 339 adult OHCA victims, excluding victims with <5 minutes of CPR. Interruptions in CPR, summarized by chest compression fraction (CCF), longest pause, and the number of pauses greater than 10 seconds, were compared between patients receiving bag valve mask (BVM), supraglottic airway (SGA), endotracheal intubation (ETI) via direct laryngoscopy (DL), and ETI via video laryngoscopy (VL). Secondary outcomes included first pass success and the effect of multiple airway attempts on CPR interruptions.Results : During the study period, paramedics managed 23 cases with BVM, 43 cases with SGA, 148 with DL, and 125 with VL. There were no statistically significant differences between the airway groups with regard to longest compression pause (BVM 18 sec [IQR 11–33], SGA 29 sec [IQR 15–65], DL 26 sec [IQR 12–59], VL 22 sec [IQR 14–41]), median number of pauses greater than 10 seconds (BVM 2 [IQR 1–3], SGA 2 [IQR 1–3], DL 2 [IQR 1–4], VL 2 [IQR 1–3]), or CCF (0.92 for all groups). However, each additional attempt following failed initial DL was associated with an increase in the risk of additional chest compression pauses (relative risk 1.29, 95% confidence interval 1.02–1.64). Such an association was not observed with additional attempts using VL or SGA. First pass success was highest with SGA (77%), followed by between DL (68%) and VL (67%); these differences were not statistically significant.Conclusions : While summary measures of chest compression delivery did not differ significantly between airway classes in this observational study, repeated attempts following failed initial DL during cardiopulmonary resuscitation were associated with an increase in the number of pauses in chest compression delivery observed